Factors motivate audiences engagement on Zafesha Facebook advertising post / Mohammad Arif Hanif Sadan - Sadan, Mohammad Arif Hanif (2018)
Social media begin to expand and it could be powerful marketing platform if business owner can utilize it. But, to utilize social media, marketeers have to know the key to bring it success. By using Facebook Ads, it can boost advertising for some products, more efficient than Television advertising. It is because Facebook have billions of active users. By using FB Ads, it will much cost saving rather than other media, but if marketeers don't know how to tackle the bidding algorithm, it could be expensive. By adapting user and gratification theory, this study main purpose is to find out what is the most motivating factor that influences user to keep engaging with business Facebook advert. If we master that most influence factor, we can produce the most quality advertising. And then, with high quality content, we can tackle the problem of low rate of post engagement and indirectly redUce the cost of Facebook Ads. Low cost of advertising will lead to higher profit margin.